A DFT study on the kinetics and mechanism of cyclodiglycine thermal decomposition in the gas phase. (June 2016) - Khavani, Mohammad; Izadyar, Mohammad; Mehranfar, Aliyeh
Theoretical investigations using density functional theory have been performed on the kinetics and mechanism of cyclodiglycine (piperazine-2, 5-dione) thermal decomposition in the gas phase. Five major possible paths have been proposed and analysed. α-Lactam, β-lactam, 4-imidazolidinone and smaller species such as HNCO, H2 CNH, H2 CCO, CO, H2 and HCN can be produced through these paths. The route yielding aziridine and HNCO is the optimum channel for this reaction from the energy point of view. Finally, according to the quantum theory of atoms in molecules, electron localisation function and localised orbital locator analyses, it was confirmed that a concerted mechanism operates for the reaction and all critical bonds of the transition states have covalent character.